2010
DOI: 10.1136/jnnp.2009.189639
|View full text |Cite
|
Sign up to set email alerts
|

A diffusion tensor MRI study of patients with MCI and AD with a 2-year clinical follow-up

Abstract: Subtle brain diffusivity changes occur from the prodromal stages of AD, mainly in posterior brain regions, and spread over the course of the disease to involve the frontal lobe. In aMCI, the severity of microstructural damage within and beyond the medial temporal lobe is associated with an increased short-term risk to develop AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 43 publications
4
64
0
Order By: Relevance
“…For example, DTI has been shown to differentiate AD patients from cognitively healthy controls with accuracy rates on par with gray matter volume estimates obtained using structural MRI [7]. In fact, some studies [8] found no predictive value in volumetry data for conversion to AD from its prodrome, mild cognitive impairment (MCI), in the short-term (2 years), whereas DTI measures were predictive. Diffusivity in the hippocampus, a key region for memory formation that is particularly susceptible to AD-related neurodegeneration [9], may predict progression from MCI to AD more accurately than hippocampal atrophy measured by structural MRI [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, DTI has been shown to differentiate AD patients from cognitively healthy controls with accuracy rates on par with gray matter volume estimates obtained using structural MRI [7]. In fact, some studies [8] found no predictive value in volumetry data for conversion to AD from its prodrome, mild cognitive impairment (MCI), in the short-term (2 years), whereas DTI measures were predictive. Diffusivity in the hippocampus, a key region for memory formation that is particularly susceptible to AD-related neurodegeneration [9], may predict progression from MCI to AD more accurately than hippocampal atrophy measured by structural MRI [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the hippocampus, MD is also elevated in other brain regions in those with AD versus healthy controls or MCI controls, including entorhinal cortex [19], temporal [19], parietal [8,19], frontal [19], and occipital lobe regions [8] as well as lateral temporal and parietal lobe association cortices [18]. Such findings of increased MD are assumed to result from the degeneration of physiological barriers to diffusion (i.e., reduced cellular membrane in neurons from stunted axons and dendrites, neuron loss) [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…44 Some studies satisfied both NINCDS-ADRDA and DSM-IV criteria, 22,23,[26][27][28]31,38 and others used only one set of criteria. Some studies that used NINCDS-ADRDA criteria adopted probable AD, 10,12,14,17,[19][20][21]23,[26][27][28][29]32,33 whereas other studies did not indicate the diagnosis as probable or possible AD. Our study excluded other types of dementia, not AD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our sample is more heterogeneous than the MCI subgroups in other studies Fellgiebel et al, 2006;Müller et al, 2007;Scola et al, 2010). Second, in our study, we applied the previously validated CSF contamination model by Koo et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on GM MD in AD reported increases of hippocampal MD and whole brain GM MD in subjects with mild cognitive impairment (MCI) as compared to healthy controls Eustache et al, 2016;Fellgiebel et al, 2004;Müller et al, 2005;Scola et al, 2010), as well as in MCI patients that converted to AD compared to MCI subjects that remained stable over a period of several years (Douaud et al, 2013;Fellgiebel et al, 2006;Scola et al, 2010;van Uden et al, 2016). In some studies, hippocampal diffusivity even demonstrated a higher diagnostic and prognostic accuracy than hippocampal volume (Fellgiebel et al, 2006;Kantarci et al, 2005;Müller et al, 2007).…”
Section: Introductionmentioning
confidence: 99%